The Value of Information. - Feltham, Gerald A. (The Accounting Review, 1968)
In recent years accountants have increased the emphasis on their role as suppliers of information for management decisions. This is partly a broadening of the scope of accounting and partly a recognition that more and better information can be produced. Accountants and other information producers must play a key role in deciding which information should be produced. However, the methodology for making these decisions is lacking. This article assumes that the criterion for designing information systems is that value should exceed cost. The purpose of the article is to provide a framework for determining the value of a change in the information system. In order to achieve this, the article formally develops individual components that are required to calculate the expected payoff for a particular information system. Relevance has been suggested as an important criterion for selecting information. In fact, many authors consider that a signal can only be called information if it is relevant to some decision by the receiver, i.e., relevant information is a redundant term. These discussions usually imply that a signal is relevant if its receipt changes the decision. Thus, relevance requires specification of both a decision maker and a decision.